ChemInform Abstract: Structure Elucidation of Verucopeptin, a HIF‐1 Inhibitory Polyketide—Hexapeptide Hybrid Metabolite from an Actinomycete. Issue 12 (March 2016) - Yoshimura, Aya; Nishimura, Shinichi; Otsuka, Saori; Hattori, Akira; Kakeya, Hideaki
Abstract: The absolute stereochemistry of the title compound is determined and its inhibitory activity in hypoxia inducible factor‐1 assays is examined.